Correlation Between Chronic Tinnitus Distress and Symptoms of Depression: A Systematic Review - Meijers, Sebastiaan M.; Rademaker, Maaike; Meijers, Rutger L.; Stegeman, Inge; Smit, Adriana L. (Frontiers in Neurology, 2022)
Objective: In this systematic review we aim to evaluate the evidence regarding the correlation between tinnitus distress and the severity of depressive symptoms in chronic tinnitus patients. Also the prevalence of clinical relevant depressive symptoms scores in chronic tinnitus patients was evaluated. Methods: We performed a systematic review in PubMed, EMBASE and the Cochrane library in June 2021 using the terms ‘depression’ and ‘tinnitus’ and synonyms, following PRISMA guidelines. Studies were selected on relevance and critically appraised regarding risk of bias using the Newcastle-Ottowa Quality Assessment Scale. Results: 1912 articles were screened on title and abstract after removal of duplicates. 33 (1.5%) articles were included for final analysis. Only cross-sectional cohort studies and case-control studies with a low level of evidence and a high risk of bias due to study design and patient selection were found. Statistical significant correlations between the experienced tinnitus distress and depressive symptoms were reported in 31 out of 33 studies. Clinically relevant depression scores had a prevalence of 4.6%-41.7%. Conclusion: In this systematic review, in which mostly cross sectional studies were included, a statistical significant correlation was found between the experienced tinnitus distress and the reported severity of symptoms of depression in chronic tinnitus patients. A wide range of clinically relevant depression scores were reported in included studies. Due to the high risk of bias of included studies it is not possible to provide a definite answer on the existence of this relationship. Future population based studies are necessary to provide more clarity.